The long-term beneficial effects of stent angioplasty on blood pressure in renal artery stenosis - Yavuzkir, Mustafa; Dagli, Necati; Ilkay, Erdogan; Karaca, Ilgin; Balin, Mehmet; Arslan, Nadi; Celiker, Hueyin (Turkish Soc Cardiology, 2005)
Objectives: Although short-term results of renal angioplasty with stent placement are well-established in the treatment of renovascular hypertension, its long-term effects remain controversial. In this study, we aimed to evaluate the long-term effects of stent therapy on blood pressure control in renal artery stenosis. Study design: The study included 26 patients (17 males, 9 females; mean age 59 years; range 43 to 75 years) who had renovascular hypertension and ostial-proximal arteriosclerotic renal artery stenosis above 70%. Twenty-five patients had unilateral stenosis. The mean stenosis rate, stent diameter, length, and follow-up period were 83.2 +/- 5.9 percent, 7.11 +/- 0.3 mm, 15.36 +/- 2.2 mm, and 2.8 years, respectively. Results: The procedure was fully successful with no major adverse events. Three patients (11.5%) died during the follow- up period. Although the mean systolic and diastolic pressures significantly decreased at 24 hours after stenting, no significant differences were noted between the values measured at 24 hours and those obtained in the following period (p> 0.05). Blood pressure was controlled by 81% within nine months, and by 69% throughout the follow-up period, during which medicaments were discontinued in six (23.1%), were reduced in 12 (46.2%), remained unchanged in four patients (15.4%), and were increased in one patient (3.9%). The mean creatinine level showed an insignificant decrease (p> 0.05). Two patients developed restenosis (7.7%) which was treated with by balloon angioplasty. Conclusion: Our findings suggest that the beneficial effect of stent placement on blood pressure is not confined to the short-term in renal artery stenosis.
Renal arter stenozunda stent uygulamasinin kan basinci üzerine uzun dönemli etkisi
Keywords: Angiography; antihypertensive agents/therapeutic use; arteriosclerosis/complications; blood pressure/drug effects; creatinine/blood; dilatation; hypertension; renovascular/therapy; renal artery; renal artery obstruction/radiography/therapy; stents